Anemia and Hyperplastic Gastritis in a Giant Anteater (Myrmecophaga tridactyla) due to Physaloptera magnipapilla Parasitism - Lértora, Walter J.; Montenegro, María; Mussart, Norma B.; Villordo, Gabriela I.; Negrette, Marcial S. (Brazilian Journal of Veterinary Pathology, 2016)
A free living female adult of Myrmecophaga tridactyla was captured in an area of deforestation in Salta Province of northwest Argentina, for subsequent relocation in Iberá Park. Three days after entering the quarantine it died with clinical signs of anorexia and ascites. It presented severe hypochromic microcytic anemia, hypoproteinemia and increase of CPK, AST and LDH on blood analysis. Grossly, there were ascites, hydrothorax, pulmonary congestion and severe catarrhal hyperplasic gastritis. The gastric mucosa was diffusely hyperemic with two clusters of numerous Physaloptera magnipapilla attached in the fundic region. Fundic mucosa was irregular with convoluted surface and covered with abundant brown-yellow catarrhal exudates. Microscopically, the gastric mucosa had well described punctate areas (pit-like structures) at points of P. magnipapilla attachment. Additionally, there were mucous hyperplasia of gastric glands and focal fibrosis with scarce infiltration of plasma cells, lymphocytes, multinucleated giant cells and eosinophils in the underlying lamina propria. This report describes a case of anemia and hyperplastic gastritis due to Physaloptera magnipapilla parasitism in a free-living Myrmecophaga tridactyla.